Expert questionnaire on the issue of economical use of the railway traffic path capacity and buildings preparation on the railway - Pavel Purkart; David Vodák (Acta Polytechnica CTU Proceedings, 2023)
The railway traffic path capacity and the issue of railway buildings planning are topics that are widely discussed in professional groups. Experts often do not the same opinions on these topics. The issue of the allocation of railway traffic path capacity is given in general legislation and further by regulations or directives of a particular railway operator. Carriers are obliged to agree to these conditions. In the case of railway buildings planning, there are also comprehensive defined procedures and selected methods and models which are used to evaluate buildings planning (for example, a four-stage transport model or a logit model). However, it is appropriate to deal with the idea of whether all these procedures are correct and whether it is not appropriate to make changes, especially in the long-established procedures, that would better reflect the current and future reality and society needs.